Mathematical analysis of COVID-19 dynamics in Iraq utilising empirical data - Wasan I. Khalil; Ayad R. Khudair (Results in Control and Optimization)
This study examines the impact and transmission of COVID-19 in Iraq via the development of a mathematical model grounded in the SIIhR framework. We assess and quantify the biological parameters of the model utilising empirical data. To ascertain the model’s reliability, we examine the existence and uniqueness of a positive solution. Utilising the validated model, we establish an optimal control problem aimed at minimising daily infections via vaccination, employing a cost function. We also present algorithms utilising Pontryagin’s minimum principle, with time-delay modifications, to identify the optimal vaccination strategy.